Tourniquet‐induced common peroneal nerve injury in a pediatric patient after knee arthroscopy – raising the red flag. Issue 9 (20th July 2017) - Saw, Kah Ming; Hee, Hwan Ing
Key Clinical Message: Peripheral nerve injury following the use of arterial tourniquets is a rare but potentially debilitating complication. Further education on the safe and appropriate practice of tourniquets is imperative to reduce the incidence of tourniquet‐related complications. Abstract : Peripheral nerve injury following the use of arterial tourniquets is a rare but potentially debilitating complication. Further education on the safe and appropriate practice of tourniquets is imperative to reduce the incidence of tourniquet‐related complications.